Some New Generalized Retarded Gronwall-Like Inequalities and Their Applications in Nonlinear Systems - Haiyong Qin; Xin Zuo; Jianwei Liu (Journal of Control Science and Engineering)
The Gronwall inequalities are of significance in mathematics and engineering. This paper generalizes the Gronwall-like inequalities from different perspectives. Using the proposed inequalities, the difficulties to discuss the controllability of integrodifferential systems of mixed type can be solved. Meanwhile, two examples as their applications are also given to show the effectiveness of our main results.